A Survey of traditional natural dye practice of Sri Lanka Today: A possible path pointing towards the development of the natural dye industry - G. M. RANATHUNGA; I. H. R. KALUARACHCHI; U. G. S. WIJAYAPALA; P. V. M. KARUNARATHNE (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The research aims to unearth cultural norms for using natural dyes that can be adapted for modern clothing production. The ability to dye with natural pigments is compared to synthetic dyes. Natural dyeing problems include a lengthy extraction process, moderate colorfastness to washing and light, and a lack of availability in large quantities, making them some of today’s most pressing research priorities. To achieve more vibrant colors, most modern users of natural dyes resort to fixing agents containing heavy metal chemicals, which negatively affect environmental health. Sustainability in clothing has recently emerged as an important metric for the fashion industry.Method: Primary data was gathered through in-depth, descriptive interviews with people who have been using natural dyes for a long time in their craft. Black clay dyeing and the process of dying Buddhist robes with indigo have both been used for centuries. As practiced traditionally, natural dyes, mordants, fixing agents, and washing and drying practices are documented.Findings: It was discovered that plants producing milky sap, tannin such exudations, and mud dyeing are effective fixing agents for producing more vibrant colors.Implications/Novel Contribution: In this study, we propose the true concept of natural dyeing, which can be used as a selling point when promoting naturally colored goods.